A novel bacterial l‐arginine sensor controlling c‐di‐GMP levels in Pseudomonas aeruginosa. Issue 10 (8th September 2018) - Paiardini, A; Mantoni, F; Giardina, G; Paone, A; Janson, G; Leoni, L; Rampioni, G; Cutruzzolà, F; Rinaldo, S
Abstract: Nutrients such as amino acids play key roles in shaping the metabolism of microorganisms in natural environments and in host–pathogen interactions. Beyond taking part to cellular metabolism and to protein synthesis, amino acids are also signaling molecules able to influence group behavior in microorganisms, such as biofilm formation. This lifestyle switch involves complex metabolic reprogramming controlled by local variation of the second messenger 3′, 5′‐cyclic diguanylic acid (c‐di‐GMP). The intracellular levels of this dinucleotide are finely tuned by the opposite activity of dedicated diguanylate cyclases (GGDEF signature) and phosphodiesterases (EAL and HD‐GYP signatures), which are usually allosterically controlled by a plethora of environmental and metabolic clues. Among the genes putatively involved in controlling c‐di‐GMP levels in P. aeruginosa, we found that the multidomain transmembrane protein PA0575, bearing the tandem signature GGDEF‐EAL, is anl ‐arginine sensor able to hydrolyse c‐di‐GMP. Here, we investigate the basis of arginine recognition by integrating bioinformatics, molecular biophysics and microbiology. Although the role of nutrients such asl ‐arginine in controlling the cellular fate in P. aeruginosa (including biofilm, pathogenicity and virulence) is already well established, we identified the firstl ‐arginine sensor able to link environment sensing, c‐di‐GMP signaling and biofilm formation in this bacterium.